Formulation of fumed silica grease from waste transformer oil as base oil - Nur Suhaila, Anang Japar; Mohd Aizudin, Abd Aziz; Mohd Najib, Razali (Egyptian Petroleum Research Institute, 2019)
This study aimed to formulate fumed silica (FS) grease using waste transformer oil (WTO) and to investigate the grease properties. Various unexplored application of the reused WTO due to its reusable characteristic. WTO and fresh transformer oil (ITO) were used as grease base fluid and the properties of oil and grease were evaluated using ASTM International standards and SKF’s Grease Test Kit. The oil and grease chemical compound were determined using Fourier Transform-Infrared Spectroscopy at wavenumber of 500–4000 cm−1. It was found that WTO have high viscosity index of 96 and low moisture content of 0.05% after pre-treatment than ITO. FS greases with and without MoS2 were classified as NLGI 2 greases when FS content was 8%. Grease formulated with MoS2 shows better performances in term of corrosiveness, oil bleed within −15% to +15%, oil separation less than 4%, and dropping point of >300 °C. FTIR results shows no significant different between ITO and WTO, and between all formulated greases. Based on the findings, it was concluded that WTO can be utilized as an alternative base oil in grease formulation due to the good properties exhibited by the formulated WTO-based FS grease blended with MoS2.